Human capital as a determinant to access finance for South African women entrepreneurs - Kowo, Kumbirai (My University, 2016)
The purpose of this research is to investigate human capital and social capital as determinants to access to finance for women SMME owners in South Africa. The study focuses on Human capital which encompasses social capital and looks at access to finance within the South African context. It does not include all other factors discussed in entrepreneurship theory. The major theories underlying this research are Social Network theory and Human capital theory. Human capital theory is viewed as formal education, skills attained and knowledge gained through informal knowledge such as prior work experience, industry experience and apprenticeship opportunities. These variables are assessed to see if they determine access to finance; which is a barrier to entrepreneurship in South Africa for SMME owners. This constraint is stressed in all The Global Entrepreneurship Monitor (GEM) reports from 2009 to 2014. This paper focuses on a single gender; females and assesses these capital factors as determinants to access finance for their entrepreneurial activity. Social capital as a factor is studied as a component of Human capital and two variables are assessed: strong ties and weak ties. Access to finance is evaluated as both debt and equity for entrepreneurs. Bivariate analysis was used to test the theories for results. The results showed an importance of human and social capital for entrepreneurs in running their businesses however not all human and social capital factors were confirmed to entirely determine access to finance for the women entrepreneurs. This study can potentially assist SMME owners within South Africa, financial institutions, policy makers and support organisations for women-owned businesses with insight into what determines accessing finance for business.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Masters in Management: Entrepreneurship and New Venture Creation Johannesburg, 2015 (March 2015)
Keywords: Women-owned business enterprises--South Africa--Finance; Businesswomen--South Africa; Entrepreneurship--South Africa; Small business--South Africa--Finance; Human capital--South Africa